2000
DOI: 10.1086/302702
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Pathogenic Mutations in Patients with Early-Onset Dementia Detected by Sequence Analyses of Four Different Genes

Abstract: Clinical differential diagnosis of early-onset dementia (EOD) includes familial Alzheimer disease (FAD) and hereditary prion disease. In both disease entities, postmortem brain histopathological examination is essential for unambiguous diagnosis. Mutations in the genes encoding the presenilins (PS1 and PS2) and amyloid precursor protein (APP) are associated with FAD, whereas mutations in the prion protein (PrP) gene are associated with prion disease. To investigate the proportion of EOD attributable to known g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
94
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(106 citation statements)
references
References 42 publications
8
94
0
1
Order By: Relevance
“…Mutation screening of dementia has shown that prion disease is a frequent cause of inherited early onset dementia. Finckh et al, 14 for example, tested four genes (APP, PSEN1, PSEN2 and PRNP) in 36 patients with familial early onset dementia and found PRNP accounted for 4/12 mutation positive cases. A general epidemiological account of IPD is problematic, however, for a number of reasons.…”
Section: Inherited Prion Diseasementioning
confidence: 99%
“…Mutation screening of dementia has shown that prion disease is a frequent cause of inherited early onset dementia. Finckh et al, 14 for example, tested four genes (APP, PSEN1, PSEN2 and PRNP) in 36 patients with familial early onset dementia and found PRNP accounted for 4/12 mutation positive cases. A general epidemiological account of IPD is problematic, however, for a number of reasons.…”
Section: Inherited Prion Diseasementioning
confidence: 99%
“…Three kinds of known mutant genes cause familial AD (FAD): mutants of amyloid precursor protein (APP), presenilin (PS) 1, and PS2 (Shastry and Giblin, 1999). The most frequent causes for FAD are the mutations in PS1, whereas only a few mutations were found in PS2 (Cruts and Van Broeckhoven, 1998;Finckh et al, 2000). Among FAD-linked mutations of APP, V642 mutations to I, F, and G are the most popular cause (Hardy, 1992).…”
mentioning
confidence: 99%
“…27,29 In these individuals immunization with a prion vaccine would seem a rationale course of action. We previously conducted experiments to confirm that antibodies produced in response to the conformations that are structurally consistent with the diseaseassociated folding pattern.…”
Section: Discussionmentioning
confidence: 99%
“…27 For example, an inherited prion disease in humans is associated with the mutation T183A. 28,29 This mutation has been suggested to disrupt glycosylation, 28 promote structural instability and misfolding 30,31 and accelerate conversion of the α-helical to β-sheet rich conformation. 32 Independent of the specific mechanism, this mutation correlates with early onset spontaneous prion disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation